IMPLEMENTASI STRATEGI PENINGKATAN KETAHANAN PANGAN PADA DINAS PANGAN TANAMAN PANGAN DAN HORTIKULTURA PROVINSI RIAU - Rahmawati, Sapta (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
The aim of this research is to determine and analyze the implementation of strategies for increasing food security at the Food Crops and Horticulture Department of Riau Province. The research type is descriptive qualitative. The number of research informants was 13 people with the Head of the Riau Province Food Crops and Horticulture Service as the key informant while the extension workers and farmers were the informants. Data collection techniques using interviews and qualitative analysis techniques using typology were carried out based on the author's interpretation of the data, both written material, interviews and observations. The results of the research show that the implementation of the Food Security Improvement Strategy at the Riau Province Food Crops and Horticulture Department is not optimal. This is due to limited agricultural land, limited extension services both in terms of quantity and quality, how to use agricultural tools and on the other hand, such as increasing productivity, increasing IP 200, mechanization of agricultural tools and farmer institutions that are not yet understood by farmers. For this reason, it is recommended that the Head of the Department make the intensification and extensification program more effective by increasing technical guidance to extension workers and farmers, providing seeds both in terms of quality and quantity, fostering farmer cooperative institutions and increasing outreach to farmers as well as increasing the budget for food security from the Riau Bertani program.